Identification of the Incidence of Obesity in Elderly People Receiving Health Services in the Bukitsangkal Health Center Working Area - Muhammad Zulhady Akram; Najmah Najmah; Fivi Tri Ayu; Syahri Aulia Utari; Zoiw Michaela Giane Sijabat; Mawar Nuraini; Marisa Marisa; Harmadi Harmadi; Sylvia Adhiani; Nur Umi Latifah (PROMOTOR, 2026)
The prevalence of obesity in Indonesia remains high, reaching 18.8% among the elderly and continuing to rise, particularly in the 55–64 year age group. With more than one billion people worldwide living with obesity, understanding obesity patterns at the local level is increasingly important. This study aims to describe the distribution of obesity cases among elderly individuals at Puskesmas Bukitsangkal during 2024, provide a comprehensive overview of elderly obesity to support more effective prevention and management programs, and address gaps identified in existing literature. This research employed an observational design with a cross sectional approach conducted at the Bukitsangkal Health Center, Palembang, from January to December 2024. The study population included all elderly individuals registered and receiving health services in accordance with Minimum Service Standards at the health center. Data were obtained from elderly medical records containing demographic characteristics and obesity status. The main outcome showed that 23.1% of elderly individuals were classified as obese, with a higher proportion observed among women compared to men. The findings also demonstrated notable variation in the monthly distribution of obesity cases. Unexpected results included an increase in morbidity during May and a shift in morbidity patterns between genders in several months. Overall, this study enhances understanding of obesity among the elderly by illustrating its distribution and highlighting factors that may influence prevalence. The findings emphasize the need for targeted health interventions and the development of more effective obesity prevention strategies. Future research should examine diet, physical activity, and socioeconomic factors in elderly.